Prediction model by probabilistic methods for the evaluation of variables in underground mining pumping systems of variables in pumping systems in subway mining - Peralta-Rodriguez, Paul (2023)
Recurrent flooding in the mining works, deficiencies in the operation of pumps, unforeseen stoppages, and lack of water availability in the processes, affect the operations in the subway mine. The traditional solution adopted is to wait for maintenance times for its post evacuation, generating stoppages, consumption of water from the wells and inefficiency in the daily water demand. Therefore, this article presents a new approach that will expand the traditional methods by introducing a prediction model using probabilistic methods. This approach will allow the design of an optimal water distribution system, the efficient control in the maintenance and covering of the recirculated water demand inside the mine. Variables describing problems related to pump flow, pressure zoning and the type of pump distribution, either in series or in parallel in the pumping system, will be determined. Also, an average data of failure and maintenance times was collected and will be introduced to the '@risk' software where a comparison of three probabilistic methods will be generated.